2014
DOI: 10.1016/j.cell.2014.11.021
|View full text |Cite|
|
Sign up to set email alerts
|

A 3D Map of the Human Genome at Kilobase Resolution Reveals Principles of Chromatin Looping

Abstract: Summary We use in situ Hi-C to probe the three-dimensional architecture of genomes, constructing haploid and diploid maps of nine cell types. The densest, in human lymphoblastoid cells, contains 4.9 billion contacts, achieving 1-kilobase resolution. We find that genomes are partitioned into local domains, which are associated with distinct patterns of histone marks and segregate into six subcompartments. We identify ~10,000 loops. These loops frequently link promoters and enhancers, correlate with gene activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

393
9,829
23
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7,488 publications
(10,258 citation statements)
references
References 82 publications
393
9,829
23
13
Order By: Relevance
“…Rao et al also identified intriguing emergent “loop” cliques enriched in super-enhancers upon cohesin depletion 37 . We also observed such features in our primary hepatocytes using a new Hi-C browser 38 , though we note that in both cases these patterns do not resemble the sharp cis -only focal patterns of CTCF-associated Hi-C peaks commonly referred to as loops 12 . Rather, these larger patches appear to be enhanced compartmental interactions between very active regions that line up well with actively transcribed genes 38 .…”
Section: Cohesin Is Central To Chromosome Foldingmentioning
confidence: 72%
See 3 more Smart Citations
“…Rao et al also identified intriguing emergent “loop” cliques enriched in super-enhancers upon cohesin depletion 37 . We also observed such features in our primary hepatocytes using a new Hi-C browser 38 , though we note that in both cases these patterns do not resemble the sharp cis -only focal patterns of CTCF-associated Hi-C peaks commonly referred to as loops 12 . Rather, these larger patches appear to be enhanced compartmental interactions between very active regions that line up well with actively transcribed genes 38 .…”
Section: Cohesin Is Central To Chromosome Foldingmentioning
confidence: 72%
“…The co-existence of two processes with different modes and scales of action can help explain the difficulties in the field in delineating and unambiguously classifying the different features of Hi-C maps, leading to a confusing plethora of denominations and definitions 7,8,12,4042 . Our data demonstrates clearly the existence of local, cohesin-dependent, self-interacting domains identifiable as TADs.…”
Section: Two Independent Folding Principlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, DNA looping facilitates gene network formation as a single enhancer may interact with more than one promoter, and a single promoter may be contacted by more than one enhancer. Many of these interactions occur in a tissue‐specific manner and appear to be the major determinants of cell type‐specific responses 111, 113, 114, 115. Critically, many enhancers do not interact with the nearest active gene but contact gene promoters many hundreds to thousands of kilobases away through long‐range DNA looping (modelled for T cells in Figure 8).…”
Section: Enhancer–promoter Interactions Shape the Function Of Tregmentioning
confidence: 99%